2018
DOI: 10.1038/s41598-018-31065-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Toll-like receptor 3 (TLR3) gene are associated with the natural course of hepatitis B virus infection in Caucasian population

Abstract: Innate immunity can induce spontaneous hepatitis B surface antigen (HBsAg) seroclearance (SC) of hepatitis B virus (HBV) infection or transition towards an inactive carrier state. Toll-like receptor (TLR) 3 signalling has been linked to these processes. Alterations in the TLR3 gene might impair immune responses against HBV. In our study, we analysed the impact of the TLR3 polymorphisms rs3775291 and rs5743305 on the natural course of HBV infection. In this retrospective study, a Caucasian cohort of 621 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Several studies have found that genetic variants on the human leucocyte antigen (HLA)-DP gene are associated with HBsAg-seroclearance during the natural history of infection [ 64 ] or during treatment with NA [ 65 ], which seems to be consistent across different populations [ 66 ]. Other polymorphisms on genes linked to immunological function, such as the toll-like receptor 3 [ 67 ], interleukin 10 [ 68 ], and T-cell immunoglobulin and mucin domain-containing molecule 3 genes [ 69 ], have also shown to be linked to the natural progression of HBV infection and are less consistently studied [ 66 ]. There have been very few studies examining the role of genetic polymorphisms on HBsAg-seroclearance in HIV-HBV co-infected individuals, apart from the IL28B haplotype showing no association [ 70 ].…”
Section: Determinants Of Functional Cure During Treated Hiv-hbv Co-infectionmentioning
confidence: 99%
“…Several studies have found that genetic variants on the human leucocyte antigen (HLA)-DP gene are associated with HBsAg-seroclearance during the natural history of infection [ 64 ] or during treatment with NA [ 65 ], which seems to be consistent across different populations [ 66 ]. Other polymorphisms on genes linked to immunological function, such as the toll-like receptor 3 [ 67 ], interleukin 10 [ 68 ], and T-cell immunoglobulin and mucin domain-containing molecule 3 genes [ 69 ], have also shown to be linked to the natural progression of HBV infection and are less consistently studied [ 66 ]. There have been very few studies examining the role of genetic polymorphisms on HBsAg-seroclearance in HIV-HBV co-infected individuals, apart from the IL28B haplotype showing no association [ 70 ].…”
Section: Determinants Of Functional Cure During Treated Hiv-hbv Co-infectionmentioning
confidence: 99%
“…TLR3 is activated at the transcriptional level by interferon regulatory factors 3 and 7 (IRF3, IRF7). IFN-β expression also regulates initiate antiviral immunity, but can cause liver damage and necrosis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mDC using TLR3 ligands leads to improved NK cell function in CHB infection (Tjwa et al, 2012). Deterioration: TLR3 polymorphism rs3775291 was associated with an increased risk of developing CHB (Geng et al, 2016;Fischer et al, 2018). Protection: TLR3 restricts WNV replication in neurons and antagonizes against NS1 (Daffis et al, 2008;Wilson et al, 2008).…”
Section: Antiviral Effects Of Tlr3mentioning
confidence: 99%
“…Wang K et al (2010) found that messenger RNA (mRNA) levels of TLR3 increased in CHB in the active phase, suggesting that TLR3 may play a vital role in starting innate immunity. Nevertheless, recent reports showed that the TLR3 polymorphism rs3775291 was associated with reduced spontaneous hepatitis B surface antigen (HBsAg) seroclearance (SC) of HBV infection and an increased risk of developing CHB (Geng et al, 2016;Fischer et al, 2018).…”
Section: Antiviral Effects Of Tlr3mentioning
confidence: 99%